Digi Maths: Impact of Technology on Mathematics Teaching in Classroom - Mittal, Vaishali; Kaushik, Namrta (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics teaching has been facing the challenge of reducing the fear of mathematics among students at school level from a very long time. An effective teaching and learning of mathematics at this level has been a challenge for school teachers.  Technology can be a very effective way of addressing the above problems and improve the teaching learning of mathematics in classrooms. Although effectiveness of technology in classroom depends on various factors but an in depth study of its implications can help us in improving our pedagogies.  In this Action Research study, we tried to find out the difference in technology enhanced mathematics classrooms and traditional classrooms with respect to students academic achievement and student motivation. We also hoped to find that how teachers and students can use technology effectively in classrooms and what type of use can be done. In order to do the above study we took two experimental groups of students studying in Class VI, and taught them the same concept separately in technology enhanced classroom and in traditional classroom. We analyzed the performance of the students in both the classrooms by taking written tests and classroom observations. Our analysis showed that technology can enhance student academic achievement and can motivate students to a large extent. A well planned integration of technology in school curriculum can result in achieving much higher goals of mathematics teaching